The impact of microplastic pollution on human health - current issues - Kucharczyk, Emilia; Andrzejczak, Klara; Sternak, Agata; Witkowski, Wiktor; Kazimierska, Maja; Błaszczyszyn, Katarzyna; Gaweł-Dąbrowska, Dagmara (Ecological Questions, 2025)
In recent years, the pervasive presence of microplastics in various environments has raised global concern. These tiny plastic fragments, less than 5mm in size, have infiltrated terrestrial, aquatic, and atmospheric ecosystems, posing threats to biodiversity, human health, and ecological balance. Understanding microplastic pollution has become crucial for scientists, policymakers, and stakeholders. This paper offers a comprehensive overview of microplastics, covering their sources, distribution, fate, and ecological implications. By synthesizing existing knowledge and identifying research gaps, this paper aims to deepen our understanding of microplastic’s global impact and support sustainable environmental management. The objective of this study is to explore the prevalence, distribution, environmental implications, and potential mitigation approaches related to microplastics across diverse ecosystems, with a specific emphasis on their impact on human health and well-being. To obtain up-to-date information concerning trends in the topic of microplastics, a review of the PubMed and Google Scholar databases, along with the latest legislative reports in both Europe and Poland, was performed. Microplastics pose a significant environmental and health threat, disrupting soil properties, biochemical cycles, and ecosystems globally. Despite extensive research, gaps remain in understanding their behavior. Effective management requires comprehensive waste strategies and regulatory measures to mitigate their impact. Addressing this challenge demands interdisciplinary collaboration and heightened public awareness for a sustainable future.